Penerapan Metode Syllabic Method pada Pelajaran PAI dalam Rangka Meningkatkan Kemampuan Membaca Permulaan Cerita Kisah Nabi dan Rasul Siswa Sekolah Dasar - Jaenullah, Jaenullah (Attractive : Innovative Education Journal, 2022)
The background of this research is because elementary students' skills in understanding and practicing reading skills are still low. Therefore, the use of the syllabic method is the right method in learning PAI, especially in reading the stories of the Prophet and Apostles. Students will understand more quickly and their learning outcomes will certainly increase. This study uses a qualitative approach as a scientific method often used and carried out by a group of researchers in the field of social sciences, including education. The results showed that the results of the posttest that had been carried out in learning early reading skills using the syllabic method for grade 1 students at SDN 1 Buana Sakti, in the aspects of assessing pronunciation, intonation and reading fluency, showed a good improvement. Students become enthusiastic and motivated in the PAI learning process on the story of the Prophet and Apostles. Keywords: Applying Syllabic Method, Increasing Reading Comprehension, Syllabic Method